Job Insecurity Sebagai Variabel Pemoderasi dalam Hubungan Ketidakpastian Lingkungan Pada Kinerja Pegawai Inspektorat Provinsi Bali - Chitra Anandari Pemayun, Tjokorda Istri; Andika Pradnyana Wistawan, I Made (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p26, 2019)
The purpose of this study was to determine the effect of environmental uncertainty on employee performance and knowing job insecurity can strengthen the relationship between uncertainty over the performance of employees of the Inspectorate of Bali ProvinceSampling in this study using purposive sampling technique. The analysis technique used is multiple linear regression. The results showed that environmental uncertainty had no effect on employee performance, job insecurity had a negative and significant effect on employee performance, and moderating insecurity jobs strengthened the influence of environmental uncertainty on employee performance. The Inspectorate Staff of the Province of Bali is good enough in carrying out their duties, so that environmental uncertainty does not affect performance. But the Inspectorate inspector should provide motivation to grow the confidence of his employees and continue to improve teamwork in finding the latest information to make decisions and realize good governance. Keywords : Employee Performance; Environmental Uncertainty; Job Insecurity.